2019
DOI: 10.1080/22221751.2019.1698272
|View full text |Cite
|
Sign up to set email alerts
|

Survival and persistence of Nipah virus in blood and tissue culture media

Abstract: Nipah virus (NiV) infection is a newly emerging zoonosis that causes severe disease in humans. Nipah virus is one of the lesser studied of the WHO emerging pathogens for which research is a priority. Survival and persistence data is important for risk management and understanding the hazard of the virus for laboratory and health care workers that may work with the virus and we present some initial findings on the survival of Nipah virus in blood and tissue culture media under different conditions. The titre of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Transmission via pigs potentially occur through the respiratory route, but close contact with infected tissues of pigs might also result in NiV transmission [23,[64][65][66]. When examining the risk for transmission that might involve bodily fluids, Smither and colleagues [67] showed that the stability of NiV in blood or cell culture media under distinct conditions can last up to 1 week at room temperature, and, hence, providing the opportunity to cause fatal infections for a longer time period. Despite transmission of Henipavirus via contaminated food [68], bats, or intermediate hosts, spread from infected persons to naïve individuals is a high-risk factor.…”
Section: The Threat Of a Potential Global Spreadmentioning
confidence: 99%
“…Transmission via pigs potentially occur through the respiratory route, but close contact with infected tissues of pigs might also result in NiV transmission [23,[64][65][66]. When examining the risk for transmission that might involve bodily fluids, Smither and colleagues [67] showed that the stability of NiV in blood or cell culture media under distinct conditions can last up to 1 week at room temperature, and, hence, providing the opportunity to cause fatal infections for a longer time period. Despite transmission of Henipavirus via contaminated food [68], bats, or intermediate hosts, spread from infected persons to naïve individuals is a high-risk factor.…”
Section: The Threat Of a Potential Global Spreadmentioning
confidence: 99%
“…Other procedures shown to effectively inactivate NiV-infected cells include the heat and ultraviolet (UV) inactivation of sera previously spiked with NiV [ 12 ], desiccation, and pH-dependent inactivation [ 13 ]. It is also known that, under optimal conditions, NiV can persist for several days in blood, culture media, urine and flesh fruit [ 13 , 14 ]. While it is essential to make sure that viruses are inactivated, it is frequently also necessary to ensure that, during the inactivation process, viral proteins and/or nucleic acid are at least partially preserved for quantification or for research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research analyzed the persistence of other priority pathogens, including Ebola virus, SARS-CoV-2, and Nipah virus, on representative surfaces or solutions ( 14 , 26 , 27 ) . Ebola virus and SARS-CoV-2 persisted in wastewater similarly to LASV under the same experimental conditions ( 14 , 26 ).…”
Section: Discussionmentioning
confidence: 99%